Binding of Cyanine Fluorescent Probes to DNA - Romancová, Ingrid (Jihočeská univerzita, 2013)
This master thesis is focused on theoretical study of the Cy3 and Cy5 dyes and their interactions with DNA. The main aim was to find the mot populated conformations of the Cy3-DNA and Cy5-DNA complexes. A comparison with the experimental structure was also done and the influence of the cyanine dyes on the conformational changes of the DNA chain was evaluated.
Binding of Cyanine Fluorescent Probes to DNA
Keywords: molecular dynamics; cyanine dyes; DNA; molecular dynamics; cyanine dyes; DNA